MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK MELALUI PENDEKATAN SAINTIFIK PADA ANAK USIA DINI - Pratiwi, Sindy (LPPM Universitas Muhammadiyah Cirebon, 2024)
In the framework of community service for students at the State Islamic University of North Sumatra in Silo Lama Village, the students held several competitions for people aged 5-10 years. The competitions held included short surahs for women and the call to prayer for men. The purpose of holding this competition is to train children's courage and confidence to appear in public. As well as training children to memorize short letters with correct reading in terms of tajwid and makhroijul letters. This study uses a qualitative descriptive research type with research subjects aged 5 to 10 years. Research shows that the implementation of the call to prayer competition and memorizing short surahs has gone well, children are brave enough to appear independently in front of many people, although there are still those who have to be accompanied by their parents.